Edukasi Pencegahan Dini: Upaya Menanggulangi Pernikahan Dini di Desa Poncokusumo - Aulia, Lintang Eisya (Maliki Interdisciplinary Journal, 2025)
Early marriage is still a prevalent phenomenon in various regions of Indonesia, including Poncokusumo Village, Malang. This practice is influenced by various factors, such as cultural pressure, low education levels, economic conditions, and the role of families in determining children’s marriage decisions. In Poncokusumo Village, many early marriages occur due to the belief that marrying at a young age can reduce family economic burdens and preserve the honor of daughters. Furthermore, a lack of understanding regarding the negative impacts of early marriage also contributes to the high incidence rate. Early marriage in this village often leads to various negative consequences, such as low female education levels, limited access to decent employment, and an increased risk of maternal and child health issues. From a social standpoint, early marriage can also elevate divorce rates due to the unpreparedness of young couples mentally and emotionally in managing their married life. Therefore, more effective interventions are required through education, enhanced access to education, and community economic empowerment to reduce early marriage rates in Poncokusumo Village. With a comprehensive approach, it is hoped that this practice can be minimized, enabling children, particularly females, to have better opportunities to develop and reach their full potential.